Case Report: Repeated Transcranial Magnetic Stimulation Improves Comorbid Binge Eating Disorder in Two Female Patients With Treatment-Resistant Bipolar Depression - Sciortino, Domenico; Schiena, Giandomenico; Cantù, Filippo; Maggioni, Eleonora; Brambilla, Paolo (Frontiers in Psychiatry, 2021)
Introduction: Binge eating disorder (BED) is the most common eating disorder, affecting a large population worldwide. It is characterized by recurrent episodes of binge eating, with no compensatory behaviors. BED is often associated with psychiatric comorbidities, and still represents a challenge in terms of treatment strategies. In the last years, neuromodulation has represented a promising approach in the treatment of BED. We report the cases of two women, affected by Bipolar Disorder Type II (BD-II) and comorbid BED, whose BED symptoms improved after a course of accelerated intermittent Theta Burst Stimulation (iTBS). Methods: We carried out a clinical study, involving neurostimulation on six patients with a treatment-resistant depressive episode. The trial consisted of a 3-week accelerated iTBS treatment, delivered to the left dorsolateral pre-frontal cortex. Clinical evaluation scales (Hamilton Rating Scale for Depression, Montgomery-Åsberg Depression Rating Scale, and Young Mania Rating Scale) were administered at baseline, after 2 weeks, and at the end of the stimulation cycle. Pharmacotherapy was maintained unchanged during iTBS treatment. Patients gave their informed consent both for the protocol and for the publication. Results: The treatment was well-tolerated. Depressive symptoms only slightly improved; however, patients' binge episodes remitted completely, which was a serendipitous finding. BED symptomatology complete remission lasted up to 12 weeks follow-up. Discussion: This is the first study regarding iTBS use in BED in comorbidity with BD-II. Further research is still needed to assess the efficacy of this technique in BED treatment.